DC–DC autotransformer with un‐interrupted operating capability during DC fault. Issue 13 (18th December 2017) - Li, Mengbo; Xiang, Wang; Zuo, Wenping; Yao, Liangzhong; Lin, Weixing; Wen, Jinyu
Abstract : This study proposed a novel type of DC/DC converter, termed as un‐interrupted DC autotransformer (DC AUTO), which has capability to ride through various kinds of DC fault without blocking any devices. Firstly, the working principles and the corresponding design procedures of the un‐interrupted DC AUTO are illustrated. Then an effective control strategy is proposed to enable steady operation during both normal time and faulted condition. Finally, a 1000 MW ± 320 kV/ ± 640 kV test system is built on PSCAD/EMTDC platform to testify the technical feasibility of the proposed converter and the effectiveness of the proposed control strategy.